2007
DOI: 10.1111/j.1365-2249.2007.03396.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Toll-like receptor 4 in peripheral blood leucocytes and serum levels of some cytokines in patients with ankylosing spondylitis

Abstract: SummaryToll-like receptor 4 (TLR4) is a member of the Toll-like receptor family, which can bridge innate and adaptive immune responses. Activation of the TLR4 signalling pathway may induce the release of proinflammatory cytokines such as tumour necrosis factor (TNF)-a and interleukin (IL)-12, which was considered to play an important role in pathogenesis of immune-mediated diseases. Ankylosing spondylitis (AS) is an immune-mediated disease whose aetiology remains unknown. The aim of the study was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 30 publications
(29 reference statements)
2
34
1
Order By: Relevance
“…TLRs 4 and 5, 135,136 NLRP2 137 and CLEC4D 136 were all shown to be differentially expressed. Interestingly TLR4 was also shown to be up regulated at both RNA and protein level in AS PBMCs in a candidate gene study 138 as well as in degenerative intervertebral discs. 139 A role for the innate system in AS has long been postulated due to the proposed link between an as yet unknown pathogen and disease onset.…”
Section: Circulating Cell Studiesmentioning
confidence: 99%
“…TLRs 4 and 5, 135,136 NLRP2 137 and CLEC4D 136 were all shown to be differentially expressed. Interestingly TLR4 was also shown to be up regulated at both RNA and protein level in AS PBMCs in a candidate gene study 138 as well as in degenerative intervertebral discs. 139 A role for the innate system in AS has long been postulated due to the proposed link between an as yet unknown pathogen and disease onset.…”
Section: Circulating Cell Studiesmentioning
confidence: 99%
“…However, it remains to be determined if these innate cell populations are able to produce other IL-23-dependent cytokines such as IL-17F, IL-21 and IL-22, and which cell population would play a pathogenic or protective role in AS pathology. Interestingly, serum IL-12p70 levels have been reported to be elevated in AS patients compared to healthy controls (Yang et al, 2007). This finding indirectly suggested the role of Th1 cell activation in AS pathology.…”
Section: 8) Ankylosing Spondylitis (As)supporting
confidence: 54%
“…In a study by Yang ZX et al, serum sTRAIL levels were found to be significantly higher in patients with ankylosing spondylitis than those in RA patients and healthy controls but no significant difference was found between the RA group and healthy controls. As a reason for this finding, it is thought that sTRAIL might have largely passed to the synovial fluid and might be associated with apoptosis of synovial fibroblasts (14). In another study, sTRAIL level measured in RA synovial fluid was found to be significantly higher than that measured in osteoarthritis synovial fluid (19).…”
Section: Resultsmentioning
confidence: 88%
“…It is well known that TRAIL expression is enhanced in T cells and, as a result, monocyte apoptosis is increased in patients with SLE (7), whereas TRAIL-R1 is increased in ductal cells by IFN-g stimulation and these cells become susceptible to apoptosis in Sjogren's syndrome (8). It has been observed that the soluble TRAIL level is significantly higher in some neoplastic (9), infectious (10), and autoimmune diseases such as SLE (11)(12)(13) and ankylosing spondylitis (14,15).…”
Section: Introductionmentioning
confidence: 99%